Pathways into treatment for eating disorders: A quantitative examination of treatment barriers and treatment attitudes. Issue 6 (2nd November 2018) - Griffiths, Scott; Rossell, Susan L; Mitchison, Deborah; Murray, Stuart B; Mond, Jonathan M
ABSTRACT: Most individuals with eating disorders do not receive treatment for their eating disorder. Closing this "treatment gap" requires a quantitative examination of individuals' attitudes towards accessing various types of treatment and of individuals' perceived barriers to seeking treatment. Thus, we recruited a sample of 425 individuals with either diagnosed or undiagnosed eating disorders and asked them to complete a survey assessing treatment attitudes, treatment barriers, and eating disorder symptom severity. Undiagnosed individuals reported more positive attitudes towards novel Internet- and smartphone-delivered treatments, and stronger barriers relating to eating disorders mental health literacy, than diagnosed individuals. Nevertheless, both diagnosed and undiagnosed individuals were broadly more positive towards established (i.e., non-novel) treatments than novel treatments. The strongest barriers to seeking treatment were fear of losing control, fear of change, and finding motivation to change. Eating disorder symptoms were positively associated with the strength of most treatment barriers. Results were broadly unchanged after adjusting for individuals' past experiences of treatment. In conclusion, the development and dissemination of novel treatments and the provision of eating disorders mental health literacy may offer promising potential pathways into treatment for individuals with undiagnosed eating disorders. Nevertheless, researchers must pay attention to and improve, individuals' attitudes towards accessing these novel treatments. The positive correlations of symptom severity with treatment barrier strength highlights the importance of early intervention for individuals with eating disorders. Finally, the fear of losing control may be a uniquely salient treatment barrier for individuals with eating disorders that requires greater attention in future research on eating disorder treatment seeking.